How did households in Mali cope with covariate shocks between 2018 and 2023? Exploration of a unique dataset - Marivoet, Wim; Hema, Aboubacar (CGIAR, 2024)
The objective of this analysis is to gain more insight into the coping behavior of households in Mali when facing covariate shocks and stressors of different kinds. To achieve this, we rely on a unique dataset, which consists of eleven waves of cross-sectional household data combined with an extensive list of shock indicators compiled from external sources. Apart from a detailed profiling of both dimensions, this analysis relies on a data mining algorithm to uncover interesting associations between covariate shocks and coping strategies. Among the main findings of this study is the pronounced diversity in shock and coping profiles observed across time and place, which in turn complicates any straightforward identification of common and consistent patterns in household coping behavior. This said, political violence has increased over time; food prices hiked in 2018, 2022 and 2023; rainy seasons were underperforming in 2021 and 2023; extreme weather events reached a peak in 2021; while the Gao region in 2023 suffered from all five shock domains at the same time. While fewer households resorted to coping over time, those who did combined slightly more strategies – which either points to increased inequality or generalized depletion of coping potential. Further, poor and erratic weather conditions appear to be important triggers for households to disinvest in farming and livestock activities, with food secure people being more inclined to resort to emergency coping when shocks prevail. This analysis also very much reveals the need for additional research on the same integrated and enhanced dataset.